1985
DOI: 10.3109/10915818509078677
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic and Chronic Toxicity Studies of 2,4-Dinitrotoluene. Part II. CD® Rats

Abstract: Subchronic and chronic toxicities of 2,4-dinitrotoluene were studied in CD® rats. Feeding of 2,4-dinitrotoluene for 13 weeks at a low dose of 34 mg/kg per day in males and 38 mg/kg per day in females caused depressed weight gain. The middle dose of 93 and 108 mg/kg per day, respectively, was toxic, caused reticulocytosis and splenic hemosiderosis, and decreased spermatogenesis. The high dose of 266 and 145 mg/kg per day, respectively, was more toxic and lethal. Some rats had widespread and stiff-legged gaits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
6
13
0
Order By: Relevance
“…This may be due to rats' reduced food consumption of feed containing 4A2NT and toxic effect of test chemical (Tables 6 and 7). The other reductive metabolite, 2A4NT, in subchronic toxicity study also showed decreased body weight gain in diet up to 169 mg/kg/d for male and female rats and 128.7 for male and 136.6 mg/kg/d for female mice 5 The subchronic study hematological results showed decreases in HGB, HCT, and RBC levels in male and female rats, suggestive of anemia that were also reported with parent compounds 2,4-DNT in rats and mice of subchronic toxicity 19,20 and other nitroaromatic compounds such as 2,4,6-trinitrotoluene (TNT) 21,22 and 1,3,5-trinitrobenzene (TNB). 23,24 There were no biologically meaningful differences in the hematological parameters studied.…”
Section: Discussionsupporting
confidence: 65%
“…This may be due to rats' reduced food consumption of feed containing 4A2NT and toxic effect of test chemical (Tables 6 and 7). The other reductive metabolite, 2A4NT, in subchronic toxicity study also showed decreased body weight gain in diet up to 169 mg/kg/d for male and female rats and 128.7 for male and 136.6 mg/kg/d for female mice 5 The subchronic study hematological results showed decreases in HGB, HCT, and RBC levels in male and female rats, suggestive of anemia that were also reported with parent compounds 2,4-DNT in rats and mice of subchronic toxicity 19,20 and other nitroaromatic compounds such as 2,4,6-trinitrotoluene (TNT) 21,22 and 1,3,5-trinitrobenzene (TNB). 23,24 There were no biologically meaningful differences in the hematological parameters studied.…”
Section: Discussionsupporting
confidence: 65%
“…The amino-nitrotoluenes were intermediates in anaerobic DNT transformation, but the final products were not clearly identified [8]. The toxicity tests performed using Mutatox and green algae bioassays have confirmed that the inter metabolite products of nitroaromatic organics released under anaerobic conditions are very toxic [8,11].…”
Section: Introductionmentioning
confidence: 80%
“…No effects on serum IgE were observed [19,30]. The mid-dose animals had a greater decrease in weight gain, reticulocytosis, hemosiderosis in the spleen, and decrease or cessation of spermatogenesis.…”
Section: Mammalian Oral Toxicity: Subchronicmentioning
confidence: 99%
“…Occasional neurological symptoms, such as straddling gait, were observed in some high-dose rats but without accompanying histopathological lesions [30,34]. Toxicity occurred in the mid-dose animals and included anemia, decreased weight gain, indicators of liver toxicity, and incidences of mammary tumors.…”
Section: Mammalian Oral Toxicity: Chronicmentioning
confidence: 99%